Die Sprache der Mainzer Republik (1792/93). Historisch-semantische Untersuchungen zur politischen Kommunikation - Herrgen, Joachim (Reihe Germanistische Linguistik, 2000)
Mainzer Republik is the name given to the period from October 1792 to July 1793 when Mainz was French and the French and the 'Mainz Jacobins' attempted to revolutionize the population of the city. In terms of language history the Mainzer Republik represents a sharp caesura. It was the first time in German history that a political part-public took shape displaying a close-knit and highly innovative form of persuasive communication. This monograph looks especially at the historical semantics and pragmatics of the Mainzer Republik, centering its argumentative focus on the interdependence between language and society.